Pretreatment of red gypsum for value-added application - Sun, Jian Meng (2022)
Red gypsum is a mineral-rich in iron and it is the by-product of the sulfuric acid process of the Ilmenite-based industrial titanium dioxide process. The characterisation of red gypsum is reviewed in this study. It was found that the presence of iron sulphate in red gypsum is one of the impurities that restricted its reutilization. The implementation of the pretreatment method for red gypsum separation is to reduce disposal to the landfills. At the same time, the products which should be natural gypsum can proceed into a value-added application such as cement production. Three pretreatment methods that do not require complicated equipment setup and have simplified procedures are studied: mineral carbonation, acid leaching and hydrothermal treatment. These pretreatment methods are reviewed based on their objective, material and equipment used, parameter studies, mechanisms, and feasibility. The efficiency of mineral carbonation, acid leaching and hydrothermal methods were 26.31% (70 bar of CO2 pressure, less than 45 μm of particle size and 200 ºC of temperature), 93.14% (0.5 M of concentration of H2SO4, 60 minutes of reaction time, 70 ºC of temperature and 1:12.5 g/mL of solid-liquid ratio) and 99% (1.5 M HCl as mineraliser, 10 mL/g of liquid-solid ratio, 6 hours of reaction time and 140 ºC of temperature), respectively. Besides, the material and energy costs of three pretreatment methods were also performed in this study. The total cost required for mineral carbonation, acid leaching and hydrothermal methods were RM 13040.41, RM 5460.32 and RM 6461.85, respectively. The justification of the best pretreatment method for red gypsum separation was based on environmental, cost and efficiency perspectives. This study showed that the mineral carbonation method is an environmentally friendly method to store carbon dioxide in solid carbonates. However, the efficiency of this method was very low, so the products cannot be used for other applications as the impurity content was still high. Although the cost required for the acid leaching method was lower than hydrothermal treatment, the purity of products for hydrothermal treatment was higher. Therefore, the overall products’ benefit would be higher than the acid leaching method. As a result, the best pretreatment method for red gypsum separation is the hydrothermal treatment method.